Executive functioning before and after onset of alcohol use disorder in adolescence. A TRAILS study. (July 2016) - Boelema, Sarai R.; Harakeh, Zeena; van Zandvoort, Martine J.E.; Reijneveld, Sijmen A.; Verhulst, Frank C.; Ormel, Johan; Vollebergh, Wilma A.M.
Abstract: Introduction: The aim of the present study was to investigate whether executive functioning (EF) in early adolescence predicted alcohol use disorder (AUD) in late adolescence and whether adolescents with AUD differed in maturation of EF from controls without a diagnosis. Methods: We used the data from the Tracking Adolescents' Individual Lives Survey (TRAILS), a cohort of 2230 Dutch adolescents. Working memory, inhibition, and attention were measured at ages 11 and 19. At age 19, lifetime DSM-IV diagnoses were determined, resulting in a control group ( n = 1111) and two AUD groups, i.e., alcohol abusers ( n = 381) and alcohol dependents ( n = 51). Regression analyses assessed whether EF at age 11 predicted the transition to AUD in late adolescence and whether AUD affected maturation of EF from age 11 to 19. Results: EF in early adolescence did not predict AUD in late adolescence. A significant interaction effect emerged between gender and alcohol dependence for shift attention (β = 0.12, SE =0.36), with girls showing smaller maturational rates. This effect remained significant after controlling for alcohol intake (ages 16 and 19) and comorbid psychiatric disorders. Discussion: Our results do not replicate the finding that EF in early adolescence is a significant predictor of AUD in late adolescence. Furthermore, for the majority of tasks, adolescents with AUD do not differ in EF maturation over the course of adolescence. Alcohol dependent girls however, show less maturation of shift attention. This is independent of the quantity of alcohol intake, which could suggest that non-normative maturation of EF is associated with the behavioural components of AUD. Highlights: Longitudinal study of executive functioning in adolescents with alcohol abuse and dependence. Large population cohort ( n = 2230) with measures of EF before and after onset of the disorder. Weaknesses in executive functioning at age 11 do not predict AUD at age 19. Quantity if alcohol intake is the most important predictor of AUD. Girls with alcohol dependence show deviant maturation of attentional shifting.